Medium-sized mammals in an urban park of Xalapa, Veracruz, México and local knowledge about wildlife - Ramos-Luna, Jorge; Sandoval-Comte, Adriana; González-Casas, I. Akemy; Serio-Silva, Juan Carlos (Therya Notes, 2023)
Wildlife inventories are key elements for the study of biological diversity and useful tools to increase public awareness on environmental topics. This study provides insights into the medium mammals that roam the Jardín de las Esculturas, a 2 ha park located in the capital of the state of Veracruz, México, in which no previous work on mammals has been conducted. Data was obtained as part of an environmental education-focused project, through camera-trapping stations and informal interviews with park employees. We report as the first time an inventory of medium-sized mammals for this site. A total of 5 orders were registered, 7 families and 10 species, 8 of which are local fauna. None of these species are under any risk category, although the loss of greenspaces and socio-environmental conflicts could eventually lead to their extirpation and local extinction, along with their ecological roles. Employees noted that the human influence of nearby settlements has had several adverse effects on local wildlife. We highlight the importance of this area as a part of the larger archipelago of forests fragments and greenspaces of Xalapa, while also mentioning the relevance of designing environmental education programs to increase public knowledge of local wildlife, their biology and conservation.